Changes in membrane fatty acids of a halo-psychrophile exposed to magnesium perchlorate and low temperatures: Implications for Mars habitability - García-Descalzo, Laura; Lezcano, María Ángeles; Carrizo, Daniel; Fairén, Alberto G. (Frontiers in Astronomy and Space Sciences, 2023)
The presence of perchlorate salts in aqueous solutions bears two opposite effects on habitability. On the one hand, perchlorate salts trigger a decrease in the freezing point of the aqueous solutions, resulting in stable aqueous solutions at subzero temperatures, thereby widening the habitable conditions for potential microbial life. On the other hand, the presence of perchlorates in solution imposes a significant osmotic stress that compromises the integrity of microbial cell membranes, thereby restricting the habitable conditions in the same aqueous environment. Here we investigated the survivability and the changes in the composition of membrane fatty acids (FAs) of the bacterium Rhodococcus sp. JG-3 cells under warm (20°C), cold (4°C), and subzero temperatures (−10°C and −16°C), and in the presence (8 wt% and 16 wt%) and absence of magnesium perchlorate (Mg(ClO4)2). Bacterial cell survivability decreased with decreasing temperature and presence of magnesium perchlorate. However, Rhodococcus sp. JG-3 was able to tolerate up to 8 wt% Mg(ClO4)2 at −16°C. The presence of magnesium perchlorate in the medium decreased the concentration of total FAs, likely due to a destabilization of the molecules by the chaotropic effect of the perchlorate anion. At the maximum stress (both subzero temperatures and 16 wt% magnesium perchlorate), the composition of FAs changed, i.e., Rhodococcus sp. JG-3 cells increased the relative abundance of saturated FAs (SFAs) over the unsaturated (UFAs) or branched (BFAs). These changes in the proportion of FAs types may be a physiological response during cooling, aimed to improve lipid membrane stability. Interestingly, the composition and relative abundance of fatty acid types (i.e., SFAs, UFAs and BFAs) of Rhodococcus sp. JG-3 when simultaneously exposed to subzero temperatures and 16 wt% magnesium perchlorate was similar to that following freezing stress alone, suggesting that either both conditions triggered a similar response or that one response dominated over the other. Our findings contribute to understand the survivability and adaptation of extremophilic microorganisms under polyextreme conditions, such as those existing in the Martian subsurface today and/or in the past, which include the documented presence of magnesium perchlorate salts in ancient sediments and global cold temperatures.